A STRATEGIC ANALYSIS FOR COMMERCIALIZATION OF HIGH SPEED ELECTRICAL MACHINE - RAHMAN, MUHIB NOOR; BASU, NILANJAN (2014)
High-speed electrical machines (HSM) are considered to be a maturing technology and are currently being applied to a range of application. This field has been extensively researched over the last few years due to advancement in their enabling technology and their potential impact in current and future application area. Cummins Inc., a global leader in diesel engine manufacturing and its associative technologies, is one of the major organizations actively researching and supporting the development of high-speed machines that can expand beyond the current design range and limitation of existing HSM. To enhance collaborative research, the organization has established an innovation centre for electric machines research. The objective of this study was to explore potential commercialization path for the machine. This includes mapping the technology through understanding of its benefits, exploration of potential application and benefits and technology to the application. Another part of the project involved researching into potential markets to understand market attractiveness due to size, competitor rivalry, and routes to market, potential customer base and strategic fit. In summary, directional assessment of the commercial potential of high speed machines are to be discovered through this study.